Typhlocharis Dieck, 1869 (Coleoptera: Carabidae, Anillini): a new species from the Iberian Peninsula, with notes about its relationships and the evolution of the diecki species group - Andújar, Carmelo; Lencina, José Luís; Serrano, José (Zootaxa, 2008)
A new species of the genus Typhlocharis Dieck (Coleoptera: Carabidae, Anillini), T. martini, described from the upper Segura River (province of Albacete, southeast Spain), is included in the diecki group characterised by a series of 4 +3 setae in the lateral umbilical series and a reduced number of preapical and apical dentiform projections of the elytron. A key to the eight species of the diecki species group is included. The relationships of the new taxon and the hypotheses about the evolutionary history of Typhlocharis and the diecki species group are discussed.